IDENTIFIKASI PERFORMA ALGORITMA BLAKE3 UNTUK VALIDASI DATA - Ariq Muhammad Thabrani; Yusup Miftahuddin (Universitas Palangka Raya, 2023)
This study aims to test the ability and performance of the BLAKE3 algorithm in determining data integrity. The test will conduct a series of trials using the checksum method to obtain the hash value of a data using the BLAKE3 algorithm. The parameters tested are computation time, power consumption, CPU thread, and data size. This test shows that the BLAKE3 algorithm is able to validate data. With this test, the use of the BLAKE3 algorithm has optimal parameters that can be set in order to get the fastest and most efficient results of computing time and power consumption.